Anatomi Konflik Komunikasi dalam Penanganan Neglected Tropical Disease di Media Sosial - Herlina Agustin; Dadang Rahmat Hidayat; Dandi Supriadi (Ultimacomm: Jurnal Ilmu Komunikasi, 2019)
Cases of snakebite resulting casualties have been found almost all over the world. In Indonesia, thereis only a few official information about them. However, the fact shows that the number of fatalitiesin Indonesia is considerably high. Approximately, more than 100,000 snakebite victims per year havebeen reported. The sparse data is caused by the lack of serious attention from all parties, includingthe government. As a result, there are so much misinformation and confusion regarding the handlingof snakebites amongst communities, including physicians. Snakebite Accident Indonesia is the onlyinformational service about snake bites available on social media platforms. The service in a formatof the Facebook closed group is the source of information that referred the most by snakebitevictims. However, communication conflicts frequently happen because of the heterogeneous of thisgroup where the members came from a variety of backgrounds and understandings. Thisphenomenon becomes the main interest of this study because the conflicts have affected the crucialefforts to handle snake bites that hang the life of people on a thread. By implementing the case studymethod, this research raises the anatomy of the communication conflict. The results indicate theinvolvement of primordialism, socio-cultural, economic, and psychological problems within theconflict. To overcome this problem, a communication system, especially concerning health issues, isneeded to bridge the dispute. The need is crucial because the conflicts must be minimized to supportcontinuous efforts of educating people.Keywords: communication conflicts, snake bites, facebook, world health organization, healthcommunication